(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
This article analyzes the effect of stress on the immune system and the mechanism of development of psychosomatic diseases from a scientific and psychological point of view. It is explained that excessive production of cortisol through the hypothalamic-pituitary-adrenal axis (HPA), which is activated in response to stress, leads to a weakening of the immune system, increased inflammatory processes, and an increased susceptibility of the body to infections and chronic diseases. It also describes in detail the mechanism of the formation of psychosomatic diseases - cardiovascular, digestive, skin, autoimmune and other stress-related disorders - resulting from prolonged psycho-emotional stress.